2012
DOI: 10.1111/j.1744-7976.2012.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Consumers’ Preference and Willingness to Pay for Country‐of‐Origin‐Labeled Beef Steak and Food Safety Enhancements

Abstract: While previous studies have investigated country‐of‐origin effect from various angles, the extent to which Country‐of‐Origin Labelling (COOL) affects U.S. beef imports from specific countries remains unexplored. Using data from 1,079 consumers from the United States, we examined consumers’ willingness to pay (WTP) for Canadian and Australian beefsteaks. We also estimated WTP for bovine spongiform encephalopathy (BSE)–tested traceability‐enabled, tenderness‐assured, and natural beef. The results from both a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 51 publications
8
77
1
4
Order By: Relevance
“…These findings differ from studies developed by other authors in the so-called "more advanced" markets. In a survey conducted by Lim et al (2013), it was found that the American consumers were willing to pay more for meat with sensorial and sanitary quality guarantee.…”
Section: Discussionmentioning
confidence: 99%
“…These findings differ from studies developed by other authors in the so-called "more advanced" markets. In a survey conducted by Lim et al (2013), it was found that the American consumers were willing to pay more for meat with sensorial and sanitary quality guarantee.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results in Table 6, the willingness to pay for a certain attribute is calculated using the following formula (Lim et al, 2013):…”
Section: Wtp Estimatesmentioning
confidence: 99%
“…Following Lim et al (2013) [46], the WTP for the kth attribute from sub-group g can be calculated as follows:…”
Section: Sub-group Analysismentioning
confidence: 99%
“…The design of choice experiments (CE) can nearly simulate real-world purchasing decisions where, for example, a farmer has to select a product from a set of options [26][27][28]. Karousakis and Birol (2006) used a CE approach to estimate farmers' demand for recycling services in the United Kingdom and more worldwide applications can be found [29][30][31][32]. In particular, Pek and Jamal (2011) used the approach to assess the effectiveness of waste disposal options in Malaysia [33].…”
Section: Theoretical Frameworkmentioning
confidence: 99%